Complementarity between Internal R&D and R&D Cooperation in the Context of Spanish Technological Opportunities - Guisado-González, Manuel; Guisado-Tato, Manuel; Ferro-Soto, Carlos (Review of Business Management, 2014)
In this paper, we analyse the existence of complementarity between the internal R&D activities and the R&D cooperative agreements of Spanish innovative manufacturing firms. This analysis is conducted concerning to the context of technological opportunities (industrial and non-industrial) and companies’ protection mechanisms (legal and strategic). The database used is the Community Innovation Survey referring to the Spanish economy. The discussion about the results is performed once the coefficients have been obtained by the Heckman correction method. The results indicate evidence of substitutability between internal R&D and R&D cooperation, and non-industrial technological opportunities and strategic protection mechanisms have no influence on innovation output. In addition, we found that non-industrial technological opportunities increase the probability of innovation in companies, although they have no influence on their innovative performance. In contrast, industrial technological opportunities do not contribute to increasing the likelihood of innovation, but influence their innovative performance.